Developing an Adaptive Curriculum for 21st-Century Competencies: An Islamic Education Management Perspective - Wiwik Wida Farwati; M Afifuddin Afandi; Faizatul Widat (Al-Qalam Institue, 2026)
This study aims to analyze the development of a 21st-century competency-based adaptive curriculum from the perspective of Islamic education management in Islamic higher education. Rapid technological developments and global educational transformations require educational institutions, including Islamic schools, to design adaptive, contextual, and competency-oriented curricula. This study uses a descriptive qualitative approach with a single case study design. Data were collected through participant observation, semi-structured interviews, and documentation studies. Data analysis refers to the interactive model of Miles, Huberman, and Saldana, which consists of data condensation, data presentation, and conclusion drawing. The findings indicate that understanding of the adaptive curriculum concept among stakeholders is still partial and uneven. The implementation of the adaptive curriculum has not been systematically institutionalized and largely relies on individual teacher initiatives. The strongest supporting factors are innovative school leadership, teacher commitment, and foundation support, while major obstacles include limited digital infrastructure, inadequate teacher training, and cultural barriers related to students' reluctance to express critical opinions. This study also formulates an Adaptive Curriculum Management Model consisting of four cycle phases: needs analysis, 4C-based planning, responsive implementation, and cycle evaluation. This research provides theoretical and practical contributions to the development of adaptive curriculum management in Islamic educational institutions, especially private madrasas that face the challenges of 21st century education.